Association between visual acuity and prospective fall risk in generally healthy and active older adults: the 3-year DO-HEALTH study - Wieczorek, Maud; Isler, Marlis; Landau, Klara; Becker, Matthias D.; Dawson-Hughes, Bess; Kressig, Reto W.; Vellas, Bruno; Orav, Endel John; Rizzoli, René; Kanis, John A.; Armbrecht, Gabriele; Da Silva, José António P.; et al. (Journal of the American Medical Directors Association, 2024)
Objective - Although aging has a strong impact on visual acuity (VA) and falls, their interaction is understudied in generally healthy older adults. This study aimed to examine if and to what extent baseline VA is associated with an increased risk of all and injurious falls over 3 years in generally healthy community-dwelling older adults. - Design - Observational analysis of DO-HEALTH, a double-blind, randomized controlled trial. - Setting and Participants - Multicenter trial with 7 European centers: Zurich, Basel, Geneva (Switzerland), Berlin (Germany), Innsbruck (Austria), Toulouse (France), and Coimbra (Portugal), including 2157 community-dwelling adults aged 70 years and older without any major health events in the 5 years prior to enrollment, sufficient mobility, and good cognitive status. - Methods - The numbers of all and injurious falls were recorded prospectively by diary and in-person assessment every 3 months. Decreased VA at baseline was defined as better-eye VA lower than 1.0. We applied negative binomial regression models for all and injurious falls, adjusted for age, sex, prior falls, treatment allocation, study site, baseline body mass index, and use of walking aids. - Results - Among the 2131 participants included in this analysis (mean age: 74.9 years, 61.7% were women, 82.6% at least moderately physically active), 1464 (68.7%) had decreased VA. Overall, 3290 falls including 2116 injurious falls were recorded over 3 years. Decreased VA at baseline was associated with a 22% increased incidence rate of all falls [adjusted incidence rate ratio (aIRR) = 1.22, 95% CI 1.07, 1.38, P = .003] and 20% increased incidence rate of injurious falls (aIRR = 1.20, 95% CI 1.05, 1.37, P = .007). - Conclusions and Implications - Our findings suggest that decreased VA is an independent predictor of an about 20% increased risk of all and injurious falls, highlighting the importance of regular eye examinations and VA measurements for fall prevention, even in generally healthy and active older adults.